Symptomatic androgen deficiency develops only when both total and free testosterone decline in obese men who may have incident biochemical secondary hypogonadism: Prospective results from the EMAS. (23rd July 2018) - Rastrelli, Giulia; O'Neill, Terence W.; Ahern, Tomas; Bártfai, György; Casanueva, Felipe F.; Forti, Gianni; Keevil, Brian; Giwercman, Aleksander; Han, Thang S.; Slowikowska‐Hilczer, Jolanta; Lean, Michael E.J.; Pendleton, Neil; et al.
Summary: Objective: Limited evidence supports the use of free testosterone (FT) for diagnosing hypogonadism when sex hormone–binding globulin (SHBG) is altered. Low total testosterone (TT) is commonly encountered in obesity where SHBG is typically decreased. We aimed to assess the contribution of FT in improving the diagnosis of symptomatic secondary hypogonadism (SH), identified initially by low total testosterone (TT), and then further differentiated by normal FT (LNSH) or low FT (LLSH). Design: Prospective observational study with a median follow‐up of 4.3 years. Patients: Three thousand three hundred sixty‐nine community‐dwelling men aged 40‐79 years from eight European centres. Measurements: Subjects were categorized according to baseline and follow‐up biochemical status into persistent eugonadal (referent group; n = 1880), incident LNSH (eugonadism to LNSH; n = 101) and incident LLSH (eugonadism to LLSH; n = 38). Predictors and clinical features associated with the transition from eugonadism to LNSH or LLSH were assessed. Results: The cumulative incidence of LNSH and LLSH over 4.3 years was 4.9% and 1.9%, respectively. Baseline obesity predicted both LNSH and LLSH, but the former occurred more frequently in younger men. LLSH, but not LNSH, was associated with new/worsened sexual symptoms, including low desire [OR = 2.67 (1.27‐5.60)], erectile dysfunction [OR = 4.53 (2.05‐10.01)] and infrequent morning erections [OR = 3.40 (1.48‐7.84)]. Conclusions: These longitudinal data demonstrate the importance of FT in the diagnosis of hypogonadism in obese men with low TT and SHBG. The concurrent fall in TT and FT identifies the minority (27.3%) of men with hypogonadal symptoms, which were not present in the majority developing low TT with normal FT.